2002
DOI: 10.1142/s0217751x02011515
|View full text |Cite
|
Sign up to set email alerts
|

On Some Properties of a Meson

Abstract: The free energy analyzed in the framework of the quantum field theory in conjunction with the statistical model for a [Formula: see text] meson is found to undergo an expansion in the condensate wave function. The superconducting and fractal properties of the meson are found to originate from the branch-cut type of singularity in the wave function of the model in which the gauge symmetry breaking is manifest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The fractal dimension for hadron has been found to be D = 9/2 [16] when the topological dimension D T = 3. The fractal dimension indicates the measure of complexity of a system which can not be shown by the integer dimensions.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fractal dimension for hadron has been found to be D = 9/2 [16] when the topological dimension D T = 3. The fractal dimension indicates the measure of complexity of a system which can not be shown by the integer dimensions.…”
Section: Formulationmentioning
confidence: 99%
“…In the current work we have studied the fractional charges of quarks considering the fractal dimension of hadrons. In our previous works we have studied the hadron properties describing it as a fractal object with fractal dimension 9/2 [15][16][17]. We have suggested that each quark in presence of the chromo-magnetic vacuum behaves like a quasi particle in an analogy with the quasi particles in Fractional Quantum Hall Effect and their fractional charges can be attributed to the fractal dimension of the hadrons.…”
Section: Introductionmentioning
confidence: 99%
“…The wave function for pentaquark baryon has been used as obtained in the context of the statistical model [25][26][27][28] which runs as…”
Section: Mass and The Decay Width Of +mentioning
confidence: 99%
“…The statistical model, since its very inception three decades ago, has undergone various applications with success [1,2,3]. The model has a deep rooted concept of a relation between quark matter and the space embedded in it and has explained and predicted a number of interesting and bizzare features [4,5,6].…”
Section: Introductionmentioning
confidence: 99%